PERENCANAAN STRATEGI PUBLIC RELATIONS GARUDA INDONESIA DALAM MEMBANGUN KEPERCAYAAN KONSUMEN - Budi Darmawan; Nindira Cahyani; Melisa Arisanty (Metacommunication: Journal of Communication Studies, 2019)
The current development of the company is growing rapidly, a few years ago happened at this time-only recently opened routes that had not been there before. In addition, there are also many old friends who finally close because of several factors. Garuda Indonesia is one airline that has not been around long enough. Then, Garuda Indonesia still has to maintain the loyalty of its customers so that they do not move around in the presence of Public Relations. In maintaining that loyalty, Public Relations plans to maintain the loyalty of its customers. Actually, Garuda Indonesia is a company that has a pretty good corporate image, such as with Garuda Indonesia in getting awards such as the Best Cabin Cabin, 5 Star Airlines, Incorporated in the SkyTrax and SkyTeam Alliance. Then Garuda Indonesia is a full service that provides full service, people who use Garuda Indonesia airlines will be issued well. The things done in this study want to see the public relations strategy planning of Garuda Indonesia's in building consumer trust.